Colonic incarceration in an adult umbilical hernia: case report and review of literature - Vagholkar, Ketan; Joy, Nitu; Chandrashekhar, Shantanu; Rao, Pooja; Chitalia, Dhairya; Sahoo, Anmol (International Surgery Journal, 2019)
Umbilical hernia is one of the commonest ventral hernias constituting ten percent of all hernias. It affects obese individuals and has a high recurrence rate if repaired by suture techniques. Incarceration of the colon in an umbilical hernia is quite rare. A case of colonic incarceration in an umbilical hernia is presented to highlight the diagnostic and technical challenges in managing such a hernia. Contrast enhanced computerized tomography is essential to ascertain the contents. Open surgery is the main stay of treatment especially in such rare cases. A combined tissue and mesh repair provides excellent results.